Attractive targeted sugar baits for malaria control in western Kenya (ATSB-Kenya): enrolment characteristics of cohort children and households - Alice Kamau; Kizito Obiet; Caroline Ogwang; Daniel P. McDermott; Maia Lesosky; Julia Janssen; Wycliffe Odongo; Julie R. Gutman; Jonathan S. Schultz; Wycliffe Nicholas; Brian Seda; Mercy Chepkirui; et al. (Malaria Journal)
Abstract Background In western Kenya, a cluster-randomized trial is assessing the impact of attractive targeted sugar baits (ATSBs) on malaria in children enrolled in three consecutive cohorts. Here, characteristics of children and households at enrolment, and factors associated with baseline malaria prevalence are described. Methods Children aged 1 to < 15 years were randomly selected by cluster (n = 70) from a census database. Cohorts were enrolled in March–April 2022, September–October 2022, and March–April 2023. ATSBs were deployed in March 2022. At enrolment, all participants were tested for malaria by rapid diagnostic test (RDT). After enrolment a household survey was conducted. Household structures were classified as ‘improved’ (finished walls and roofs, and closed eaves) or ‘traditional’ (all other construction). A generalized linear mixed model was used to assess factors associated with malaria prevalence. Results Of 3705 children screened, 220 declined and 523 were excluded, due to plans to leave the study area (n = 392), ineligible age (n = 64) or other reason (n = 67). Overall, 2962 children were enrolled. Bed net use the previous night was more common in children aged 1–4 years (746/777 [96%]) than those aged 5–<15 years (1806/2157 [84%], p < 0.001). Of the 2644 households surveyed (for 2,886 participants), information on house construction was available for 2595. Of these, only 199 (8%) were categorized as ‘improved’, as most houses had open eaves. While 99% of households owned at least one bed net, only 51% were adequately covered (one net per two household residents). Among 999 children enrolled in the first cohort (baseline), 498 (50%) tested positive by RDT. In an adjusted multivariable analysis, factors associated with RDT positivity included sub-county (Alego-Usonga vs Rarieda, adjusted odds ratio [aOR] 4.81; 95% CI: 2.74–8.45; p < 0.001), house construction (traditional vs improved, aOR 2.80; 95% CI: 1.59–4.95; p < 0.001), and age (5–< 15 vs 1–4 years, aOR 1.64; 95% CI: 1.13–2.37; p = 0.009). Conclusions In western Kenya, the burden of malaria in children remains high. Most households owned a bed net, but coverage was inadequate. Residents of Alego-Usonga sub-county, those living in traditionally constructed households, and older children were more likely to test positive by RDT. Additional tools are needed to effectively control malaria in this area. Trial registration The ATSB trial is registered under Clinicaltrials.gov NCT05219565